Aspects From The History Of The City Of El-Meniaa: Origins To The End Of The Modern Period (Journal of Namibian Studies : History Politics Culture, 2024)
The city of El-Meniaa has witnessed various historical stages, making it one of the ancient cities and a city that experienced significant prosperity. This can be attributed to its strategic location, as it lies in the heart of the African desert, making it a transit point for many trade caravans coming from kingdoms and countries in sub-Saharan Africa. The abundance of underground water due to the presence of a massive underground water reservoir led to the emergence of springs. The presence of terrain such as hills provided a strategic location for the construction of fortresses, and the presence of plains enriched by the waters of seasonal rivers from time to time. All of this made it a geographical center that attracted human groups seeking stability, security, and guaranteed livelihoods. The city has witnessed several developments and historical events, which turned it into a competitive hub among different ethnicities, especially during the period of conflict between the cities of Ben Zazu and Al-Qal'a. After the destruction of Ben Zazu, only the fortress built by the Zanata tribe remained, utilizing this geographical area until the arrival of the Arabs in modern times, who took control of the ancient palace. Through this research, we will present the most important historical stages that the city has gone through from its inception until the end of the modern period.